2011
DOI: 10.3390/ma4040816
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Application Researches of Porous Fiber Metals

Abstract: Metal fiber porous materials with intrinsic properties of metal and functional properties of porous materials have received a great deal of attention in the fundamental research and industry applications. With developments of the preparation technologies and industrial requirements, porous fiber metals with excellent properties are developed and applied in many industry areas, e.g., sound absorption, heat transfer, energy absorption and lightweight structures. The applied research progress of the metal fiber p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 7 publications
1
30
0
Order By: Relevance
“…Recent advances in fiber-pullout techniques have promoted the development of a new type of cellular material -MFSSs 1 (Xi et al, 2011). These porous materials consisting of metallic fiber networks can be used as structural materials as the low density core of sandwich panels (Clyne et al, 2005;Markaki and Clyne, 2003a,b;Zhou and Stronge, 2005), in addition to functional materials as anodic gas diffusion backing (Liu et al, 2004), catalyst support (Qiao et al, 2008), and filtration net (Wang, 2003), among others.…”
Section: Introductionmentioning
confidence: 98%
“…Recent advances in fiber-pullout techniques have promoted the development of a new type of cellular material -MFSSs 1 (Xi et al, 2011). These porous materials consisting of metallic fiber networks can be used as structural materials as the low density core of sandwich panels (Clyne et al, 2005;Markaki and Clyne, 2003a,b;Zhou and Stronge, 2005), in addition to functional materials as anodic gas diffusion backing (Liu et al, 2004), catalyst support (Qiao et al, 2008), and filtration net (Wang, 2003), among others.…”
Section: Introductionmentioning
confidence: 98%
“…These periodically structured materials composed of stacked metal meshes or foams, must present well-ordered morphologies with low porosity and large interconnected through pores in order to act as efficient heat sinks 21,248 . In addition to their morphology, these materials must also offer high thermal conductivity and diffusivity 16,247,249,250 . The thermal and fluid flow characteristics of such woven metal textiles were comparable to plate-fin heat exchangers while being up to 40 % lighter.…”
Section: Heat Storage and Dissipationmentioning
confidence: 99%
“…The scope of applications of porous metal frameworks includes separation membranes, 2,3 conductive porous electrodes [4][5][6][7] , biocompatible scaffolds 8,9 , sensing [10][11][12][13] , actuators 14 and hybrid composite materials 15,16 . The development of porous cellular metal materials has been driven by the need for low density and high stiffness materials in the composite-material industry [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…[12] All shapes and spatial structures of pores in the porous metallic fiber/ wires materials were irregular, intricate, and randomly distributed, e.g., non-woven wire structures, [5,6] quasiordered entangled structures, [7,8] spiral wire structures, [2] and the texture-type structure. [1,[9][10][11]20] The mechanical properties including energy absorption properties [11,19,25] and the stress-strain behavior under various loading states have been investigated. Most of the above studies revealed that the compressive behavior exhibited a plateau region with a nearly constant follow stress.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Sintered metal fibrous/wiry porous materials with traits of both metallic fibers/wires and porous materials have many attractive characteristics. [11] Several previous experimental studies have been conducted on the fabrication, microstructure, and the mechanical response of stochastic porous metallic fiber/ wire materials made of Cu, [12] Ti, [13] steel, [14][15][16][17][18] aluminum alloy, [19] and stainless steel. [1,[20][21][22][23][24][25] Raw materials of porous metallic fiber/wires materials were obtained by cutting the as-received fibers/wires produced by a bundledrawing [1,20,22] or melt extraction [21] process into straight short fibers/wires, preformed by wire distortion and twisting, [14,15] helical wire weaving, [19] and fabricated by using a multi-tooth tool cutting method.…”
Section: Introductionmentioning
confidence: 99%